The courage of Sarah Noble - Dalgliesh, Alice 1893- (Scribner, 1954)
Remembering her mother's words, an eight-year-old girl finds courage to go alone with her father to build a new home in the Connecticut wilderness and to stay with the Indians when her father goes back to bring the rest of the family.